Human Guide Training to Improve Hospital Accessibility for Patients Who Are Blind: Needs Assessment and Pilot Process Evaluation - Tyler G James; Sarah Hughes; Christa Moran; Sherry Day; Michael M McKee (JMIR Rehabilitation and Assistive Technologies)
Abstract BackgroundPeople with disabilities are a priority population for health services research. People who are blind or have low vision (B/LV) are a segment of this priority population, who experience difficulty in accessing health care facilities due to architectural and navigational barriers. These barriers persist despite disability civil rights law in the United States. ObjectiveThe purpose of this study is to report on a program that was developed to train way finders in human guide technique for people who are B/LV. MethodsThis study took place at Michigan Medicine, an academic medical center in southeast Michigan. We conducted a needs assessment through cohort discovery and soliciting expert feedback. The human guide training program was developed using the PRECEDE-PROCEED health promotion program development model and targeted health care volunteers and staff. The intended components included in-person training, a web-based module, and tip sheets. Due to COVID-19, the in-person training was not implemented. We report findings from a process evaluation, measuring reach, knowledge, behavioral capability, and satisfaction pre- and postprogram. ResultsIn total, 87 participants completed the training, and most of them were Michigan Medicine volunteers. There were significant improvements in behavioral capability related to the human guide technique. Participants were satisfied with the training and provided recommendations for more detailed demonstrations and scenarios in future training sessions. ConclusionsThe training improves participants’ knowledge and confidence in providing wayfinding assistance to patients who are B/LV. However, further in-person training is recommended to provide hands-on experience and detailed feedback. Addressing architectural barriers and providing accessible patient education materials is crucial for improving health care accessibility for patients who are B/LV.